Delayed recall memory impairment in patients with Parkinson's disease - Schelp, Arthur Oscar; Mendes-chiloff, Cristiane Lara; Paduan, Vanessa Cristina; Corrente, José Eduardo; Lima, Fabrício Diniz De; Marchette, Juliana Cristine Nunes; Luvizuto, Gustavo José; Bazan, Rodrigo (Associação de Neurologia Cognitiva e do Comportamento, 2016)
ABSTRACT Age is one of the risk factors for dementia in patients with Parkinson's disease (PDD). Distinct cognitive syndromes of Parkinson's disease (PD) have been identified in previous studies. Questions about the role of such cognitive disorders in PD outcomes, especially memory dysfunction, in patients with PD remain unanswered.Objective:To establish possible correlations between delayed recall memory (episodic memory), age, and other demographic variables in patients with PD.Methods:A two-stage protocol was applied. Patients with delayed recall memory compromise, selected based on a brief battery of tests (BBRC-Edu), were classified as dementia cases and submitted to the Mattis Dementia Rating Scale (MDRS). Data from patients with memory disturbances were compared against individuals without episodic memory impairment, and correlated with age and demographic variables.Results:Except for identification and naming, all subtests in the screening battery showed a significant difference (p≤0.0001) between the memory-compromised group (case) and the group without memory impairment (no case). The results also correlated negatively with age (p≤0.0001) and positively with level of education (p=0.0874) in patients with PD.Conclusion:The analysis showed a significant relationship between age and dementia characterized by impaired episodic memory. The findings support reports of a wide spectrum of neuropsychological performance impairment in PD with age, particularly dementia associated with memory deterioration. No correlations between disease duration and cognitive dysfunction were evident.

RESUMO Idade é um fator de risco bem determinado para surgimento de demência em pacientes com doença de Parkinson (PDD). Estudo prévio tem demonstrado diferentes distúrbios cognitivos em portadores da doença de Parkinson (PD). O significado do comprometimento da memória é pouco compreendido.Objetivo:Estabelecer possíveis correlações entre comprometimento de memória de evocação tardia (memória episódica), idade e outras variáveis demográficas em pacientes com DP.Métodos:Os pacientes foram submetidos a um protocolo dividido em duas etapas. Os pacientes com alterações na memória de evocação tardia (memória episódica), selecionados a partir de bateria breve de rastreio cognitivo (BBRC-Edu) foram classificados como portadores de demência e submetidos ao exame de rastreio para demência de Mattis (MDRS). Os dados relacionados a comprometimento da memória, foram comparados ao grupo que não apresentava alterações e correlacionados a idade e outras variáveis demográficas.Resultados:Com exceção de identificação e nominação, todos os sub-testes mostraram diferenças significativas (p≤0,0001) entre o grupo que apresentava disfunções na memória episódica e o grupo que não apresentava alterações. Foi demonstrada correlação negativa com idade (p≤0,0001) e positiva com nível educacional (p=0.0874).Conclusão:O estudo registrou correlação significativa entre idade e demência caracterizada por comprometimento da memória episódica. Os resultados dão suporte para existência de amplo espectro de disfunções associadas ao envelhecimento, em pacientes com PD. Não foram demonstradas correlações significativas com tempo de doença.
Comprometimento da memória de evocação tardia na doença de Parkinson
Keywords: Parkinson's disease; dementia; ageing; doença de Parkinson; demência; idade